CONGOLESE HIV+, NAIVE, GENOTIPO F1, GRAVIDA: CRITICITÀ IN DIAGNOSTICA BIOMOLECOLARE - R. Tenuta; F. Greco; O. Savino; S. Dodaro; M. Gallo; A.M. Lo Bianco; M. Spadafora; D. Perugini; P. Rocca; A. Noto; C. Giraldi (Microbiologia Medica, 2007)
-